2004
DOI: 10.1016/j.jacc.2003.09.065
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of cardiac masses using contrast echocardiographic perfusion imaging

Abstract: Echocardiographic contrast perfusion imaging aids in the differentiation of cardiac masses. Compared with the adjacent myocardium, malignant and vascular tumors hyper-enhanced, whereas stromal tumors and thrombi hypo-enhanced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
1
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(98 citation statements)
references
References 31 publications
0
90
1
7
Order By: Relevance
“…Beyond anatomic imaging, CMR enables tissue characterization of cardiac masses based on vascular supply. Differentiation of neoplasm from thrombus based on contrast uptake has been validated in relation to histopathology findings 7, 8, 9. Tissue characterization imaging of masses has also been shown to stratify clinical outcomes 4.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond anatomic imaging, CMR enables tissue characterization of cardiac masses based on vascular supply. Differentiation of neoplasm from thrombus based on contrast uptake has been validated in relation to histopathology findings 7, 8, 9. Tissue characterization imaging of masses has also been shown to stratify clinical outcomes 4.…”
Section: Introductionmentioning
confidence: 99%
“…Kirkpatrick et al have suggested that malignancy causes hyperenhancement in contrast echo due to its rich vascularisation. On the other hand, a complete lack of enhancement suggests the presence of thrombus 20. Cardiac MRI has been also recently extensively studied for the use for differentiating cardiac masses.…”
Section: Discussionmentioning
confidence: 99%
“…This tumour could also be a thrombus, especially in the context of neoplasia. However, the tissue aspect of this tumour, the mass linked to the septal ventricular side of the tricuspid valve and the absence of associated pulmonary embolism rather suggested metastasis 2 3…”
Section: Answer: Cmentioning
confidence: 96%